INCIDENCE OF HYPERTENSION IN ADOLESCENTS IN THE WORKING AREA OF PACCERAKKANG HEALTH CENTER AND SUDIANG HEALTH CENTER, MAKASSAR CITY - Hasliani (AKADEMI TEKNIK ADI KARYA, 2024)
Hypertension generally occurs in advanced age, but some studies suggest that hypertension can appear as early as adolescence and its prevalence has increased over the past few decades. However, many do not realize that it is the cause of hypertension in adults and the elderly. This study aims to determine the prevalence of hypertension in adolescents at the Sudiang Raya Health Center, Makassar City. The method used is carried out by observation with a Cross Sectional approach. The research sample was 147 adolescents using Two Stage Cluster Sampling. Data collection using questionnaires, measurements of weight, height and blood pressure. The data were analyzed univariately using a frequency distribution table. The results of the study obtained 73 male respondents (49.7%) and 74 female respondents (50.3%). Most (77.6%) of the respondents had a moderate level of knowledge. The results of blood pressure measurements showed that as many as 9 people (6.1%) were in the stage 2 hypertension category, as many as 18 people (12.2%) were in the stage 1 hypertension category, as many as 22 people (15.0%) were in the pre-hypertension category and as many as 98 people (66.7%) had normal blood pressure. Conclusion: The results showed that one-third of the respondents already had hypertension.